Prospective Comparison of Facial Soft Tissue Changes Using 2D Photographs and 3D Scanning After En Masse Dentoalveolar Maxillary Distalization Using Tads (Orthodontic Journal of Nepal, 2022)
Introduction: This prospective clinical study was undertaken to analyse the three-dimensional facial soft tissue changes after en-masse maxillary distalization using 3D structured light-based scanner and facial photographs and to compare the two diagnostic aids.Materials and Method: 12 Indian adult patients of 17- 23 years of age with unilateral or bilateral class II molar relationship and those indicated for en-masse distalization. A pre-operative and post-operative extra oral 3D scan and 2D photographs were obtained for each subject. A prospective comparative evaluation of 10 lateral and 20 frontal soft tissue parameters was done.Result: When pre to post comparison was made in different study parameters using paired t test, none of the study parameter showed significant difference.Conclusion: The laser facial scanning can be considered as a useful and reliable tool to analyze the circumoral region for orthodontic and orthognathic surgical diagnosis and treatment planning. The difference in facial soft tissue changes evaluated using 3D scans and 2D photographs was also not statistically significant.